Remedies before the International Court of Justice : a systemic analysis - Stoica, Victor, 1985- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2021)
"The book seeks to determine the manner in which the International Court of Justice interprets and applies the remedies generally accepted by the international community and codified by the International Law Commission in its Articles on State Responsibility. As such, it seeks to answer the following questions: i) Whether the International Court of Justice adopts a specific approach towards the remedies of international law? and ii) If yes, what are the justifications for this approach? The survey of theoretical perspectives, canvassing academic writings and subjective perspectives featured in the pleadings of the parties to the disputes, and the judgments of the Court, illustrates relevant results. The systematic analysis demonstrates that the Court has a distinct approach to the interpretation and application of remedies available in international law. While the Court is cautious in ordering precise actions from the parties, it appears to prioritize declarations regarding issues of legality"--
Jurisdiction -- Provisional measures -- Declaratory judgments -- Specific performance -- Cessation, assurances, and guarantees of non-repetition -- Restitution in kind -- Compensation -- Satisfaction -- The case law of international courts and tribunals.
Includes bibliographical references and index.
Keywords: International Court of Justice; International Court of Justice; Provisional remedies; International courts; Restitution; International courts; Provisional remedies; Restitution